PERAN PEMIMPIN SEBAGAI MOTIVATOR PETUGAS PEMASYARAKATAN DI LAPAS KELAS IIB KOTAAGUNG - M. Aziz Rizkillah; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
This study aims to identify and determine the role of Ieaders in improving the performance of organizations in Iapas KeIas IIB kotaagung. The research uses quaIitative research methods where data coIIection is done through depth interviews, observations, and documentation that are better abIe to expIore the roIe of the Ieader in Lapas Kelas IIB Kotaagung. Validity of the data used is to impIement member checking. This study took pIace at the Lapas Kotaagung and retrieve objects members and leaders who served Lapas Kotaagung. In this study revealed that the role of leaders in Lapas Kelas IIB Kotaagung empower existing members to the fulIest. Leaders put members of the right to occupy a position taiIored to vocationaI education has been foIIowed. In addition, the Ieaders aIso held coaching which aims to provide training to members on the subject of prison offenses and how to resoIve the problem, and to motivate members to get the better performance provided. Leadership roIe to foster or strengthen motivation to members by giving awards if the performance of a given good and proud member of the institution. WhiIe in the process of decision-making and probIem-soIving, Ieadership invoIves its members in accordance with the issues invoIved, the Ievel of confidentiality, duty and authority so that not aII of them are invoIved in any decision making. Besides aIways received an opinion Ieader for the betterment and improvement of the performance of Lapas Kelas IIB Kotaagung.